(3GdehLR aj GdefWb GdQjGVj (B/s - (3HhNfScj, LhRjas; (3djK, CKjQ jhSas ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2018)
(3eHGOF YGeI heaGgje hJGQjN GdefWb GdQjGVj, efWb GdLed eY bje GdUOb hGdfaj hcPdc LOhd ebGQfI ddeaGgje hGdQhGHW GdefWbjI HGdGVGaI Gdi YfUQ GdJbjje, hbhGfjf GdeSGhGI hGdbjGS hGdJMhjd, hHYOgG efWb GdeMehdGJ hGdeLehYGJHeG ajg GdbjGS heHOC GdghjI Ch GdPGJjI hGdQhGHW Hjf GdeLehYGJ eY GdJeKjd GdHjGfj hGdcjGf Gh GdhLhO hHGdJGdj MSGH GdeLehYGJ eY bhGfjf GdeLehYI GdTGedI hGdeLehYI GdNGdjI, hCNjQG efWb GdYdGbGJ hGdPj jJVef GdYdGbGJ Hjf GdYdGbGJ hGdbhGfjf GdJeGKdjI eY GdfWGb hGdMbhd hGdYdGbI GdehQhKIhGdYdGbGJ GdeJTGcdI Ch GdeJeGKdI hcPdc GdYdGbGJ GdeJYOOI , HGdGVGaI Gdi CbSGe GdefWb GdCNQi(B.s
(3eQGLY U(B.161- 179s
Keywords: (3GdefWb GdQeRj hGdQjGVjs